Hubungan Kadar Low-Density Lipoprotein (LDL) dan Body Mass Index (BMI) terhadap Kejadian Stroke pada Pasien Lanjut Usia di RSUD Raden Tumenggung Notopuro Sidoarjo Tahun 2023 - Yuhasnara, Balqis Agita; Suprapti, Herni; Budianto, Nugroho Eka Wirawan (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
This study aims to determine the relationship between Low-Density Lipoprotein (LDL) levels and Body Mass Index (BMI) with the incidence of stroke among elderly patients at Raden Tumenggung Notopuro Regional General Hospital, Sidoarjo, in 2023. This research employed a quantitative method with a case-control design, using secondary data obtained from patient medical records. The sampling technique used was non-probability sampling with a consecutive sampling approach, resulting in 112 respondents who met the inclusion and exclusion criteria. Data were analyzed using the Levene Test for homogeneity, the Mann-Whitney Test for comparison, and the Spearman correlation test. The results indicated a significant relationship between LDL and BMI with stroke incidence, with p-values of 0.000 and 0.003 (p<0.05), respectively. The correlation coefficients showed a strong positive relationship between LDL levels and stroke incidence (r=0.508), as well as a moderate positive relationship between BMI and stroke (r=0.276). It can be concluded that elevated LDL levels and imbalanced BMI contribute significantly to the increased risk of stroke among the elderly. Therefore, controlling cholesterol levels, maintaining a healthy diet, and monitoring body weight are essential preventive measures to reduce stroke risk in this population.